2017
DOI: 10.3892/mmr.2017.6673
|View full text |Cite
|
Sign up to set email alerts
|

Microglia activation triggers oligodendrocyte precursor cells apoptosis via HSP60

Abstract: Reactive microglia are present in lesions of myelin-associated white matter disorders resulting in injuries to oligodendrocyte precursor cells (OPCs). Therefore, protection of OPCs from injury due to excessive activation of microglia is important in treating these diseases. Heat shock protein 60 (HSP60) has been demonstrated to be released extracellularly in the failing heart upon stress or injury. However, the role of HSP60 in the central nervous system and whether it participates in the toxic effects of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…In another study, LPS‐activated microglia secreted heat shock protein 60 (HSP60), a stress chaperone protein that has dual functions in cell apoptosis depending on specific conditions. These secreted HSP60 were found to bind to Toll‐like receptor (TLR) 4 of OPCs and initiated its apoptotic mechanism …”
Section: Microglia‐derived Factors and Oligodendrocytes Lineage Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, LPS‐activated microglia secreted heat shock protein 60 (HSP60), a stress chaperone protein that has dual functions in cell apoptosis depending on specific conditions. These secreted HSP60 were found to bind to Toll‐like receptor (TLR) 4 of OPCs and initiated its apoptotic mechanism …”
Section: Microglia‐derived Factors and Oligodendrocytes Lineage Cellsmentioning
confidence: 99%
“…These secreted HSP60 were found to bind to Toll-like receptor (TLR) 4 of OPCs and initiated its apoptotic mechanism. 86 On the other hand, recent studies have revealed protective roles of microglia during the remyelination phase. After myelin damage in MS model, a genome-wide gene expression analysis was performed for the microglia in corpus callosum during remyelination.…”
Section: Crog Lia-derived Fac Tor S and Oli G Odendro C Y Te S Lmentioning
confidence: 99%
“…Despite that microglia are necessary for repairing the CNS in normal conditions, activated microglia suppress the processes of brain repair by inhibiting the differentiation of oligodendrocyte precursor cells into myelinating oligodendrocytes via distinct mechanisms including heat shock protein 60 production, NO‐dependent oxidative damage and TNF‐α signaling (Li, Zhang, et al, ; Pang et al, ). Following pathological alterations, extracellular adenosine triphosphate, a source of energy metabolism, produced by dead and injured neurons can in turn activate microglia via purinergic receptors (Liu & Wang, ).…”
Section: The Role Of Microglia In Neurological Diseases: Friend or Foe?mentioning
confidence: 99%
“…Depleting microglia reduces the number of OPCs in the corpus callosum and the extent of myelin formation, as seen in the marked reduction in expression of myelin-specific genes and proteins such as proteoliopid protein (PLP) and myelin basic protein (MBP; Hagemeyer et al, 2017). Microglial activation also triggers OPC apoptosis via HSP60 extracellular release and the TLR4-NFκβ signaling pathway (Li et al, 2017). These postnatal microglia are characterized by CD11c expression (and high production of Igf1) and are predominantly found in primary myelinating areas (Wlodarczyk et al, 2017).…”
Section: Myelinogenesismentioning
confidence: 99%